Step-by-step explanation:
Since the sequence above is an arithmetic sequence
For an nth term in an arithmetic sequence
A(n) = a + ( n - 1)d
where a is the first term
n is the number of terms
d is the common difference
From the question
a = 1/3
d = 1/2 - 1/3 = 1/6 or 2/3 - 1/2 = 1/6
Substitute the values into the above formula
That's
<h3>
![A(n) = \frac{1}{3} + (n - 1) \frac{1}{6} \\ = \frac{1}{ 3} - \frac{1}{6} + \frac{1}{6} n](https://tex.z-dn.net/?f=A%28n%29%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%28n%20-%201%29%20%5Cfrac%7B1%7D%7B6%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B1%7D%7B%203%7D%20%20-%20%20%5Cfrac%7B1%7D%7B6%7D%20%20%20%2B%20%20%5Cfrac%7B1%7D%7B6%7D%20n%20)
</h3>
So the nth term of the sequence is
<h3>
![A(n) = \frac{1}{6} + \frac{1}{6}n](https://tex.z-dn.net/?f=A%28n%29%20%3D%20%20%5Cfrac%7B1%7D%7B6%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B6%7Dn)
</h3>
For a50 since we are finding the 50th term
n = 50
So we have
<h3>
![A(50) = \frac{1}{6} + \frac{1}{6} (50) \\ = \frac{1}{6} + \frac{25}{3}](https://tex.z-dn.net/?f=A%2850%29%20%3D%20%20%5Cfrac%7B1%7D%7B6%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B6%7D%20%2850%29%20%5C%5C%20%20%3D%20%20%5Cfrac%7B1%7D%7B6%7D%20%20%2B%20%20%5Cfrac%7B25%7D%7B3%7D%20)
</h3>
We have the final answer as
<h3>
![A(50) = \frac{17}{2}](https://tex.z-dn.net/?f=A%2850%29%20%3D%20%20%5Cfrac%7B17%7D%7B2%7D%20)
</h3>
Hope this helps you